Media, Advertising and Other Influences on Decisions to Enter Aged Residential Care - Henderson, Robyn Elizabeth (Auckland University of Technology, 2016)
There are continued concerns, politically and socially, regarding the future growth in over 65 year olds; described as an unavoidable "demographic silver tsunami". New Zealand has a high utilization rate of aged residential care beds, compared to most other OECD countries, with some 34,000 individuals living in 600 residential facilities across the country. In tandem, with this high rate of institutional aged care, social concerns have been expressed regarding both the quality and increasing commercialization of aged care nationally. This critical discourse analysis draws on an eclectic range of critical theorists to examine the sources of power within contemporary discursive frameworks that influence older adults to enter aged residential care in New Zealand. Older adults aged between 65 years and 92 years currently residing in aged residential care were recruited into focus groups to illuminate the key influences that had supported their entry into aged residential care. In tandem with the focus group sessions a six month scan of media and advertising of residential aged care in the local area was undertaken with a view to examining the relevance of media advertising as an influencing factor in decision to enter aged residential care. Findings were that older adults are influenced into residential aged care through a complex array of discursive frameworks such as the political narrative of ageing and the social narrative of ageing, with its manifest assertion of the appropriateness of residential aged care as an accommodation solution for older adults. Finally, the analysis reviewed the critical relationships of older adults, including the values and beliefs of family and their ability to exert power and control over older adults’ lives and their decisions. The findings of this study provide a description of the decision processes and experiences of transitions to residential aged care from the perspective of those older adults directly affected. This study has identified the complexity and multiplicity of discursive forces that directly and indirectly influence such decisions made, often at vulnerable times, in older adult’s lives. These findings contribute to an enhanced understanding of the current construction of ageing in contemporary New Zealand; and strongly argue a need for review of existing models of accommodation for older adults within New Zealand society into the future.
Keywords: CDA; Residential aged care; Decision; New Zealand; Media